A Scheduling Algorithm for WDM Optical Networks - Cheah, Cheng Lai; Mohd Ali, Borhanuddin; R. Mukerjee, Malay; Prakash, V.; Selvakennedy, S. (Malaysian Journal of Computer Science, 2001)
This paper proposes a scheduling algorithm for time-slotted WDM broadcast-and-select optical networks. The algorithm is free from collision and supports a particular class of quality of service (QoS), namely constant bit rate (CBR). The running time complexity of the algorithm is O(Mlog2N) , where M and N are the number of packets used for scheduling and the number of nodes, respectively. This running time can be improved to O(log3N) by parallel processing.